An Analysis on Methods to Predict On Demand Based Online Agricultural Commodity of Selling Buying Using Social Computational Driven Models - Subramanian, Nithya Ganapathi; Akhilashri, P.S.S (International Journal of Computer Sciences and Engineering, 2025)
Consumption and demand for agricultural produce is always on high variable ends. Consumption of an agricultural produce increases the demand among consumers and also vice versa. The need for a system to predict on demand for commodity is always felt among farming commodity such that the demand for agricultural commodity can be predicted earlier and hence supported earlier. This research works on application of social computing models over understanding the trends of consumer for prediction of demand. This research works on base of online marketing along with commodity utilization demand is discussed. Subsequently, ways to improve online marketing using the concepts of social computing are proposed and implemented. Analysis predicts on application of multiple soft computational models employed over traditional online marketing methods to suggest of effective / accurate prediction